Shii Sectarianism in the Middle East: Modernisation and the Quest for Islamic Universalism. - Alagha, Joseph (Islamic Studies, 2014)
This is a good analytical book, which conveys meticulously the transformations of two prominent Shii ‘ulama’—Kashif al-Ghita’ in Iraq and Muhsin al-Amin in Lebanon—who combined authenticity with modernity. While relying on an impressive host of original primary Arabic and Persian sources, the author is gifted in employing discourse and content analysis, which can capture the attention of both academic and lay readers. The monograph’s only liability is that it is void of ethnographic research; as such it lacks fieldwork, interviews, and empirical research, things that would have blown more life into the argument and would have helped the reader conceptialise and contextualise more.